2022
DOI: 10.1158/1538-7445.sabcs21-gs3-05
|View full text |Cite
|
Sign up to set email alerts
|

Abstract GS3-05: Fulvestrant-palbociclib vs continuing aromatase inhibitor-palbociclib upon detection of circulating ESR1 mutation in HR+ HER2- metastatic breast cancer patients: Results of PADA-1, a UCBG-GINECO randomized phase 3 trial

Abstract: Background: ESR1 mutations are known drivers of resistance to first line aromatase inhibitors (AI)-based therapy in hormone receptor-positive (HR+) HER2- metastatic breast cancer (mBC) patients (pts), but their clinical actionability remains unknown. The randomized phase 3 PADA-1 trial aimed at evaluating the clinical benefit associated with a switch to fulvestrant-palbociclib upon the detection of a rising ESR1 mutation in blood (bESR1mut) in HR+ HER2- mBC pts treated by first line AI-palbociclib.. Methods: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 0 publications
0
47
0
9
Order By: Relevance
“…PADA‐1 is an ongoing ctDNA‐based interventional clinical trial, evaluating the efficacy of switching therapy upon detection of plasma ESR1 mutations in ER + HER2 − MBC. 20 Patients were initially treated with combination of aromatase inhibitors and palbociclib as line 1 treatment. In a subcohort of patients with detected “rising” ESR1 mutations, patients were randomized (1:1) into two separate treatment arms: (a) aromatase inhibitors + palbociclib; and (b) fulvestrant + palbociclib.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PADA‐1 is an ongoing ctDNA‐based interventional clinical trial, evaluating the efficacy of switching therapy upon detection of plasma ESR1 mutations in ER + HER2 − MBC. 20 Patients were initially treated with combination of aromatase inhibitors and palbociclib as line 1 treatment. In a subcohort of patients with detected “rising” ESR1 mutations, patients were randomized (1:1) into two separate treatment arms: (a) aromatase inhibitors + palbociclib; and (b) fulvestrant + palbociclib.…”
Section: Discussionmentioning
confidence: 99%
“…In a subcohort of patients with detected "rising" ESR1 mutations, patients were randomized (1:1) into two separate treatment arms: (a) aromatase inhibitors + palbociclib; and (b) fulvestrant + palbociclib.After further follow-up of 34.5 months, the median PFS of patients who switched to fulvestrant was double compared to those who remained on aromatase inhibitor, 11.9 months vs 5.7 months. Although results are preliminary, data from the PADA-1 study has indicated that early detection of plasma ESR1 mutations could guide treatment switch to another ER targeted combination with palbociclib, giving significant gain in PFS 20.…”
mentioning
confidence: 99%
“…This suggests that ctDNA assessment may be used as a surrogate of tumor progression and be complementary to radiological evaluations in MBC [39], as reported in the early setting to anticipate the disease recurrence [40,41]. In some hormone-receptors-positive MBC, ESR1 mutation detection antedates tumor progression and may be a useful biomarker to adapt endocrine therapy [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…The PADA‐1 trial 10 was also noteworthy, says Dr. Kaklamani. Results from the phase 3 PADA‐1 trial demonstrated that, among patients with hormone receptor–positive breast cancer who were treated with an aromatase inhibitor plus palbociclib, those who had an ESR1 mutation detected in their blood before disease progression doubled their median progressionfree survival after a switch to fulvestrant plus palbociclib.…”
Section: Estrogen Receptor–positive Disease Advancementsmentioning
confidence: 99%